PENGARUH FAKTOR PRIBADI, ORGANISASI DAN NON ORGANISASI TERHADAP KOMITMEN ORGANISASI KARYAWAN PADA PT. PLN AREA BUKITTINGGI - Rahmad Rahmad; Sabri Sabri; Nasfi Nasfi (Jurnal Apresiasi Ekonomi, 2020)
Organizational commitment is an interesting focus to be discussed at PT. PLN (persero) Bukittinggi area, this has led to the growing development of organizational commitment in an employee, will be able to reduce the emergence of negative work that appears in the organization, such as employee work strikes, employee demonstrations, work absenteeism numbers, feeling unlucky at work and turnover.Regarding the purpose of this study to analyze and prove personal factors on organizational commitment, analyze and prove organizational factors on commitment, analyze and prove non-organizational factors on organizational commitment and analyze and prove together personal factors, organizational factors and non-organizational factors towards organizational commitment to PT. PLN (persero) Bukitinggi Area.The population in this study were all employees and employees of PT. PLN (persero) Bukittinggi Area consisting of permanent employees and freelancers exceeding company leadership totaling more than 63 people in which the research sample used the census method for each employee in the PT. PLN (persero) Bukittinggi Area consists of 63 employees. Analysis of research data using multiple linear regression methods.The results of this study are personal factors (X1) significant to organizational commitment (Y) at PT. PLN (persero) Bukitinggi Area of 0.638 with a significance value of 0,000, organizational factors (X2) significantly influence organizational commitment (Y) at PT.PLN (persero) Bukitinggi Area of 0.091 with a significance value of 0.018, non-organizational factors (X3) significantly influence organizational commitment (Y) at PT. PLN (persero) Bukitinggi Area of 0.448 with a significance value of 0.007 and personal factors (X1), organizational factors (X2) and non-organizational factors (X3) significantly influence organizational commitment (Y) at PT. PLN (persero) Bukitinggi Area with an F value of 32,653 with α 0,000. Keywords : personal factors (X1), organizational factors (X2), non-organizational factors (X3), organizational commitment (Y)